The Boxer Codex transcription and translation of an illustrated late sixteenth-century Spanish manuscript concerning the geography, ethnography and history of the Pacific, South-East Asia and East Asia - Souza, George Bryan; Turley, Jeffrey Scott (Leiden Brill, 2016)
"In The Boxer Codex, the editors have transcribed, translated and annotated an illustrated late-16th century Spanish manuscript. It is a special source that provides evidence for understanding early-modern geography, ethnography and history of parts of the western Pacific, as well as major segments of maritime and continental South-East Asia and East Asia. Although portions of this gem of a manuscript have been known to specialists for nearly seven decades, this is the first complete transcription and English translation, with critical annotations and apparatus, and reproductions of all its illustrations, to appear in print"--Provided by publisher.
General editor's foreword -- List of drawings, illustrations and maps -- Glossary -- Part 1. Transcription -- Ladrones -- Cagayans -- Zambales -- Visayans -- Moros -- Tagalogs -- Moro customs -- Brunei -- Maluku Islands -- Java -- Rutter of Aceh / by Dom Joao Ribeiro Gaio -- Ribeiro Gaio's Rutter of Patani -- Rutter of Siam / by Dom Joao Ribeiro Gaio -- New Guinea / by Miguel Roxo de Brito -- Japan -- China's tributary neighbors -- Tai Ming / by Fr. Martin de Rada, O.E.S.A. -- Chinese imperial ceremony -- Chinese and Tatar cavalries -- Chinese deities -- Chinese bestiary -- Champa -- Part 2. Translation -- Ladrones -- Cagayans -- Sambal -- Visayans -- Moros -- Tagalogs -- Moro customs -- Brunei -- Maluku Islands -- Java -- Rutter of Aceh/ by Dom Joao Ribeiro Gaio -- Rutter of Patani / by Dom Joao Ribeiro Gaio, Antonio Dias, Henrique Mendes, Francisco Das Neves and Joao Serrano -- Rutter of Siam / by Dom Joao Ribeiro Gaio -- New Guinea / by Miguel Roxo de Brito -- Japan -- China's tributary neighbors -- Tai Ming / by Fr. Martin de Rada, O.E.S.A. -- Chinese imperial ceremony -- Chinese and Tatar cavalries -- Chinese deities -- Chinese bestiary -- Champa.
Includes bibliographical references and index.
Keywords: Ethnology -- Oceania -- History -- 16th century -- Sources; Ethnology -- Southeast Asia -- History -- 16th century -- Sources; Ethnology -- East Asia -- History -- 16th century -- Sources; Oceania -- History -- 16th century -- Sources; Southeast Asia -- History -- 16th century -- Sources; East Asia -- History -- 16th century -- Sources; Oceania -- Geography -- Sources; Southeast Asia -- Geography -- Sources; East Asia -- Geography -- Sources; Spain -- Colonies -- Asia -- History -- 16th century -- Sources